Keeping the Family Wisdom Alive through Family Storytelling - Dewi, Tribuana Tungga; Hasanah, Siti Uswatun; Chania, Ines (Universitas Mercu Buana, 2024)
ABSTRACTThere are not much research available regarding family storytelling, though this activity already proven to be effective on identity building, developing strong relationship within family member, and also as a foundation for building family values. That is why this research is conducted in order to identify the function of family storytelling and how the stories conducted. This research is conducted by qualitative method, with in-depth interview as the data collecting technique. All informants are female because research showed that the main storyteller in the family, usually are women. As a conclusion, it is identified that family storytelling practice is a very personal and unique process and each informant has a unique insight on understanding their family stories.The uniqueness might be occur because of the different dynamic and character of the family. Keywords: Family Communication, Family Storytelling, Family Stories, Family Wisdom, Family Identity.